Fear, Anxiety, and Birth Outcomes: Exploring Psychological Determinants in Labor Progress - Alfadefi Khalifatunnisak; Nareswari Diska Nugraha (Journal for Quality in Public Health, 2026)
Psychological factors such as fear and anxiety during labor have been increasingly recognized as important determinants influencing labor progression and birth outcomes. These emotional responses can alter neuroendocrine pathways, affecting uterine contractions and overall labor efficiency. Despite growing awareness, psychological determinants are still often under-assessed in routine maternity care, particularly in clinical settings. This study aims to examine the relationship between maternal fear and anxiety with labor progress and birth outcomes. A quasi-experimental study was conducted involving 60 primigravida women in the active phase of labor. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HAM-A), while labor progress was assessed using partograph monitoring. Data were analyzed using independent t-test. Mothers with lower anxiety levels demonstrated significantly faster labor progress (p < 0.001) and fewer interventions compared to those with higher anxiety levels. High anxiety was associated with prolonged labor duration and increased pain perception. Fear and anxiety significantly influence labor progress and outcomes. Addressing psychological well-being should be an essential component of maternity care.